The official Ubuntu book. - Hill, Benjamin Mako, ....-; Bacon, Jono, ....-; Krstic, Ivan, ....- (Upper Saddle River : Prentice Hall, 2007)
Ubuntu is a complete, free operating system that emphasizes community, support, and ease of use while refusing to compromise on speed, power, and flexibility. It's Linux for human beings--designed for everyone from computer novices to experts. Ubuntu is the most in-demand Linux distribution, and this official guide will get you up and running quickly. Learn how to seamlessly install and customize Ubuntu for your home or small businesses. Its open source power can be used in schools, government, or by corporations, and is suitable for both desktop and server use. The Ubuntu community is built on the premise that software should be available free of charge, and that people should have the freedom to customize and alter their software in whatever way they see fit.